Music-Nature Harmony : Event Tourism Elements and Tourist Typology - Rinaldi, Aditya Rizki; Masahengke, Enricho Gabriel; Zulfiqar, Mohamad Rafif; Pradigda, Christiano Joviel Budi (Graduate School, Universitas Brawijaya, 2025)
Experience-based event tourism has gained increasing attention, particularly through nature-based music events that integrate emotional, social, and environmental dimensions. This study examines how event design interacts with visitor characteristics in shaping tourist experiences at the Sunset di Kebun concert held at Cibodas Botanical Gardens. Using a descriptive qualitative approach, data were collected through participant observation and semi-structured interviews with 13 purposively selected visitors. The analysis integrates the 6A destination framework, VALS psychographic segmentation, and Plog’s tourist typology. The findings reveal that most visitors belong to the Experiencers and Believers segments and exhibit mid-centric characteristics. The event design—combining natural settings, music performances, educational elements, and opportunities for social interaction—contributes to emotional engagement, aesthetic appreciation, and visitor comfort. Although all six destination elements were present, only those directly perceived and experienced by visitors influenced differentiated experiential patterns across psychographic typologies. This study highlights the role of nature-based music events in fostering socially meaningful and experience-oriented tourism and provides conceptual insights into the relationship between event design and tourist typology within the context of event tourism in Indonesia.